The effect of powder type on the setting time and self compactability of mortar - Khaleel, O.R.; Razak, Hashim Abdul (Elsevier, 2012)
In this paper, fly ash and metakaolin as pozzolan while limestone powder and kaolin as filler material were used at replacement levels of 5, 10, 15, and 20 by weight of cement and sand, respectively. The effects of these powders on the fresh property of mortar mixes were studied and reported. Superplasticizer dosages were determined from flow test on cement paste and mortar with different powder content. A total of 33 mixes were prepared, mixed, and tested. The mini slump cone and mini V-funnel box tests were used to assess the flowability of the fresh mortar. In addition, the effect of mineral admixture on setting time of the mixes was also evaluated. In this study, the optimum dosage of superplasticizer was determined based on the desired flowability for self compactability. Superplasticizer at higher dosages than optimum reduced the stability due to bleeding. The results confirmed the role of the mineral powders in determining the desired stability and the flowability of mortar mixes which is crucial for self compacting concrete. Â© 2012 Elsevier Ltd. All rights reserved.